Co-operation Amongst Polish Research Libraries - Dobrzyńska-Lankosz, Ewa (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
Polish research libraries have a long tradition of co-operating with one another, particularly when certain solutions require a collective effort. Co-operation can take place either at local, national or international level. In the past, we were able to observe close co-operation at the national level between libraries in similar disciplines (for instance, co-operation of groups of medical, technical and economics libraries). This form of co-operation has existed until today. Then, at the beginning of the 1990’s a new ‘configuration’ of library co-operation was initiated, that is, co-operation between libraries in various disciplines within one consortium aimed at choosing, purchasing and implementing the same integrated library system. The next step was co-operation undertaken within an inter-system consortium in order to fund a national union catalogue. This was an enormous enterprise, whose aim was to facilitate access to catalogue information on the collections of Polish research libraries and accelerate the process of cataloguing books. The National Union Catalogue NUKAT is based on shared cataloguing. At present, the catalogue is being created by 60 libraries, mainly academic.